PENGARUH PERENDAMAN DAGING SAPI DALAM BERBAGAI KONSENTRASI BLEND JAHE (Zingiber officinale Roscoe) TERHADAP PH, DAYA IKAT AIR, DAN SUSUT MASAK - Rosita, Rosita; Husni, Ali; Riyanti, Rr; Septinova, Dian (Jurnal Riset dan Inovasi Peternakan, 2019)
The purpose of the research to determined the effect of soaking beef in various concentration of ginger blend and determined the best concentration of ginger blend on pH, water holding capacity, and cooking loss on beef. This research was conducted at the Laboratory of Animal Production and Reproduction, Department of Animal Science, Faculty of Agriculture, University of Lampung. Meat samples obtained from RPH Z-Beef Indonesia. The treatment used a completely randomized design (CRD) with four treatments and five replications. Treatments are in the form of concentration of ginger blend 0%, 10%, 20%, and 30% with immersion time for 50 minutes. The results obtained were analyzed by Analysis of Variant (ANOVA) at the 5% level and followed by the Least Significant Difference (LSD) test. The results showed that the addition of ginger blend with a concentration of up to 30% did not significantly influenced (P>0.05) on the pH value and water holding capacity, but had a significant effected (P<0.05) on the cooking loss of beef. Keywords: Ginger, Beef, Physic quality.